2019
DOI: 10.1039/c9cy00817a
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the activity of hydrogen release from liquid organic hydrogen carrier systems by sulfur-additives to Pt on alumina catalysts

Abstract: Liquid organic hydrogen carriers represent an interesting alternative for hydrogen storage and transport. We demonstrate a method to simultaneously increase the activity of LOHC dehydrogenation catalysts and reduce side product formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 39 publications
1
55
0
Order By: Relevance
“…Therefore, it is desirable to develop more selective catalysts that can suppress side reactions. Auer et al [44] found that sulfur coating of the low-coordination sites of Pt particles on Pt/Al 2 O 3 can suppress the side reactions. They also believe that the turnover rate of the reaction is improved as a result of the enhanced desorption of the dehydrogenation product, DBT, due to the change in the electronic state of Pt caused by the sulfur modification.…”
Section: Recent Reports On the Catalytic Dehydrogenation Of 18h-dibenzyltoluenementioning
confidence: 99%
“…Therefore, it is desirable to develop more selective catalysts that can suppress side reactions. Auer et al [44] found that sulfur coating of the low-coordination sites of Pt particles on Pt/Al 2 O 3 can suppress the side reactions. They also believe that the turnover rate of the reaction is improved as a result of the enhanced desorption of the dehydrogenation product, DBT, due to the change in the electronic state of Pt caused by the sulfur modification.…”
Section: Recent Reports On the Catalytic Dehydrogenation Of 18h-dibenzyltoluenementioning
confidence: 99%
“…The carrier is porous Al 2 O 3 , while the shell consists of the active component platinum. The catalyst was tuned with sulfur due to improved activity and reduced side product formation [19]. For the experiments, the microstructure was filled with particles of the fraction of 200-300 µm without dilution; thereby a total catalyst mass of 1.51 g was integrated.…”
Section: Reactormentioning
confidence: 99%
“…19 For fuel applications, especially in the maritime sector, efficient release of hydrogen from the carrier is required so a lot of research is being put into the development of new catalysts for this reaction. [128][129][130][131][132][133] Toluene and methylcyclohexane however, have quite a low flashpoint, and this implies fire hazards when using this molecule in bulk as a hydrogen carrier medium. Furthermore, even though it is still present in present day fuels, the aromatic contents have been restricted in fuels due to the proven carcinogenic nature of small aromatic molecules.…”
Section: Aromatic Liquid Organic Hydrogen Carriersmentioning
confidence: 99%